(untitled) (Horn of Africa Journal of Social Science, 2024)
As for HIV/AIDS, there is an estimate of 10,500 living with HIV/AIDS in Somalia. Children living with HIV are also estimated at 500. Among HIV positive people, only 35% attend ART centers for medications. This study aims to assess discrimination against people living with HIV/AIDS in Somalia. With the support of People Living with HIV (PLHIV), the researcher targeted 346 respondents but those accepted to participate were 187 PLHIV including 102 females and 85 males live in different regional states in Somalia. During data collection the researcher either met face to face with the respondent or communicated by telephone. The study doesn’t assess how people become HIV positive. However, the study found nearly half of the respondents became HIV positive for the past five years. Stigma and discrimination are the major challenges face PLHIV. The assessment conducted 1st Dec. 2020 – 10th Jan. 2021